Design of RSA processor for concurrent cryptographic transformations. (May 2017) - Vollala, Satyanarayana; Varadhan, V.V.; Geetha, K.; Ramasubramanian, N.
Abstract: The performance of RSA depends strongly on the competent implementation of modular multiplication and modular exponentiation. Performance can be improved in three ways: (i) by reducing the frequency of modular multiplications; (ii) by reducing the time required to evaluate modular multiplication; (iii) by increasing the RSA cores. This work proposes enhancements to the Montgomery Multiplication and also to Square & Multiply algorithm. Bit Forwarding 1-bit (BFW1) algorithm has been implemented to evaluate modular exponentiation that resulted in 11.11% improvement in throughput, and 1.90% reduction in power consumption. A Dual-core RSA processor with a hardware scheduler has been designed for performing concurrent cryptographic transformations to attain better throughput without increasing the frequency. The proposed hardware scheduler is able to increase the throughput of 95.85% for MSM algorithm and 117.61% for BFW1 for 1024-bit key with reference to the MME42_C2 algorithm. The results have been verified for a key of length 1024-bits, up to 32-cores. This is scalable, by proportionally increasing BRAM and priority queue size.